Peran Ikatan Remaja Masjid Al-Khoir dalam Syiar Islam di Desa Bubulak Tanjung Pura Karawang - Iddah Fukhoiroh; Ahmad Junaedi Sitika; Debibik Nabilatul Fauziah (ISLAMIKA, 2022)
The Mosque Youth Association is a youth association that fills activities in the mosque, fosters youth to take part in religious activities in the mosque and teaches values and norms of life according to the teachings of the Prophet Muhammad. The Mosque is a place for broadcast Islam and the task of the youth around who will invite and teach the surronding community about religion. In this study, the method used was descriptive qualitative method by conducting observations and interviews with supervisors as well as advisors, heads and administrators of the education and religious sector of the Mosque Youth Association, community leaders and local residents. The results of this study revealed that all programs designed by the administrators of the Mosque Youth Association were very good, this was seen from the responses of local residents who supported and accepted all the programs designed. However, there are still inhibiting factors from the coaching program, namely: the lack of facilities and infrastructure to support teaching and learning activities such as lack of space and lack of reading books.